A critical analysis of the effect of crosslinking on the linear viscoelastic behavior of styrene–butadiene rubber and other elastomers. Issue 8 (24th January 2013) - Prabhu, Rasika; Klitkou, Rasmus; Medvedev, Grigori A.; Caruthers, James M.
Abstract The linear viscoelastic behavior in dynamic shear and tensile creep at temperatures from −30 to 70 °C is measured for an styrene–butadiene rubber (SBR) elastomer cured with dicumyl peroxide to crosslinking densities between 0 and 23.5 × 10−5 mol/cm3. The G′, G″, and tan δ isotherms are analyzed by time–temperature superposition (TTS), where the tan δ master curves are consistent with those of Mancke and Ferry. However, to achieve the TTS in the lightly crosslinked SBR systems, an anomalous vertical shift is required in the narrow temperature region from 10 to 30 °C. The vertical shift factor in this temperature region is not the standard <![CDATA[${{\rho _0 T_0 } \mathord{\left/ {\vphantom {{\rho _0 T_0 } {\rho T}}} \right. \kern-\nulldelimiterspace} {\rho T}}$]]> <inline-graphic xlink:href="ark:/27927/pgg1v85d0gw" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> from rubber elasticity. No anomalous behavior is detected in the equilibrium modulus, which is a linear function of temperature in accordance with the classical theory of rubber elasticity. In contrast to SBR, standard vertical shifts are required to effect TTS for uncrosslinked polybutadiene and an ethylene propylene diene monomer elastomer. © 2013 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys, 2013